The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/03057925.2017.1341301
|View full text |Cite
|
Sign up to set email alerts
|

Education and countering violent extremism: Western logics from south to north?

Abstract: This paper explores the way education and conflict have become entangled together during the post-9/11 'war on terror' response to 'radical Islam' at home and abroad. The paper charts the complex ways that education has been deployed to serve Western military and security objectives in multiple locations in the global south and how these strategies have now returned to the 'West' in the form of CVE interventions. Drawing on Foucault's concept of the 'boomerang effect' I will explore whether and how education t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…Between 1984 and 1994, more than 13 million textbooks were distributed among young individuals in Afghan refugee camps and Pakistani madrasas. As these textbooks mainly consisted of hate curriculum focused on the Soviets, this led to the creation of a generation of radicalized youth [56]. In Rwanda, research has shown that the curricula and teaching methods smothered critical thinking, which impacted individuals' responses to the genocide [57].…”
Section: Poor Quality Of Educationmentioning
confidence: 99%
“…Between 1984 and 1994, more than 13 million textbooks were distributed among young individuals in Afghan refugee camps and Pakistani madrasas. As these textbooks mainly consisted of hate curriculum focused on the Soviets, this led to the creation of a generation of radicalized youth [56]. In Rwanda, research has shown that the curricula and teaching methods smothered critical thinking, which impacted individuals' responses to the genocide [57].…”
Section: Poor Quality Of Educationmentioning
confidence: 99%
“…Concerns have been raised about teachers having to report children at risk of radicalisation (e.g. Novelli 2017). Simultaneously there has been increased antiimmigrant rhetoric in the popular press.…”
Section: (Mcguiness 2017 20)mentioning
confidence: 99%
“…This was the theme of the wellattended 20 th Anniversary Symposium held in Bristol during May 2018, where the Keynote speaker Arjen Wals, Professor of Transformative Learning for Socio-Ecological Sustainability at Wageningen University in The Netherlands, argued how being 'disruptive' can play a positive role in challenging preconceptions, understanding conflict, and promoting sustainable peace (see https://cireblog.wordpress.com/blog/; Wals, Yoko and Leicht, 2017). Similarly, innovative and challenging work on violent extremism, education and sustainable peace building by Novelli and colleagues (2017;Novelli 2017), studies of inclusivity and transnational justice processes (Paulson and Bellino, 2017), and research priorities stemming from the impact of climate change and sea level rise all have urgent social justice, human rights and global security implications. Such work is vital in our times of economic, cultural and environmental uncertainty, and it highlights the importance of BAICE supporting comparative and educational research on these and related issues across and beyond traditional disciplinary boundaries.…”
Section: Conclusion : Some Implications and Challenges For Baicementioning
confidence: 99%